PEDAGOGICAL FEATURES OF ADVANCED TRAINING OF SECONDARY MEDICAL WORKERS - Kamilova Nargiza Gayratovna (Research Focus International Scientific Journal, 2026)
In the rapidly evolving healthcare environment, the advanced training of secondary medical workers (nurses, feldshers, medical assistants, laboratory technologists, midwives, and emergency technicians) has become critically important. Pedagogical features of such training include the integration of contemporary educational technologies, competency-based learning, continuous professional development (CPD), simulation-based approaches, reflective practice, and clinical mentorship. This article provides a theoretical synthesis of contemporary pedagogical strategies and their relevance to improving professional performance among secondary medical workers. Drawing on research from Uzbek, CIS, and international scholars, the study highlights the educational frameworks, challenges, and best practices for structuring advanced training programs. The findings indicate that learner-centered pedagogy, blended learning, and lifelong learning models contribute to competency enhancement, professional adaptability, and improved patient outcomes. The article concludes with recommendations for institutional policy, curriculum design, and faculty development.